A superfluous name of Premna (Lamiaceae) - Wang, Yinghui; Wang, Qiang (Phytotaxa, 2020)
While preparing the manuscript of Flora of Pan-Himalaya, volume 44(1) of Lamiaceae (Wang 2019), we encountered a species of the genus Premna Linnaeus (1771: 587), Premna velutina Wu (1977: 428), which was described by Wu (1977) in Flora Yunnanica, and was accepted in Flora Republicae Popularis Sinicae (Chen 1982) and Flora of China (Chen & Gilbert 1994). However, this is clearly a later homonym of Premna velutina Gürke (1895: 338). Thus, in Flora of Pan-Himalaya Vol. 44(1), a replaced name Premna wuana Wang (2019: 155) was proposed for this illegitimate name. Nonetheless, we actually made a superfluous name, since Boufford and Bartholomew (2012) had proposed Premna wui (noted as “wuii”) Boufford & Bartholomew (2012: 1) to replace the illegitimate name. We thought that all the names of Premna reported from the Pan-Himalaya region and other involved names had been dealt with in our Flora of Pan-Himalaya, volume 44(1). However, we are very sorry for ignoring the correct name Premna wui by mistake, and also for ignoring the name Premna cordiformis Li Bing Zhang & Y.F.Duan in Duan & Zhang (2014: 281), which is another superfluous name of Premna wui. We noticed that Li (2018) had reduced the superfluous name Premna cordiformis to a synonym of Premna wui.